Analisis Hubungan Tingkat Kesehatan Bank Terhadap Pengungkapan Identitas Etika Bank Umum Syariah - Ellen Betha Chindo; Tri Joko Prasetyo; Harsono edwin Puspita (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2022)
This research aimed to determine the correlation of bank soundness levels toward the disclosure of Islamic commercial banks' ethical identity in Indonesia. This research data collection uses secondary data derived from annual reports available on the official website of each bank. To achieve the objectives, this research was conducted by examining 12 Islamic Commercial Banks in Indonesia that have been operating from 2014-2019. The sample of this study amounted to 72 samples with the determination of the sample using the purposive sampling method. Based on the test results using the correlation test. The researcher found that the level of bank soundness based on the Financing to Deposit Ratio (FDR), Good Performance Governance (GCG), and Capital Adequacy Ratio (CAR) had a correlation with the disclosure of the Islamic commercial banks’ ethical identity. However, there is no correlation between Non-performing Financing (NPF) and Return on Assets (ROA) with the disclosure of the Islamic commercial banks’ ethical identity.